Pengaruh Pemanasan Lokal Terhadap Ketangguhan dan Laju PerambatanRetak Plat Baja "Grade B". - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan UGM, 1999)
ABSTRACT An Investigation of the effect of local heating on the fracture toughness and crack growth rate for ship plates has beee performed. The local heating was carried out using a welding system on the field to be investigated. A number of plates, which has been welded, was cut to produce a number of specimens which consists of fracture toughness specimens, crack growth rates specimens and other specimens needed. The main test in the research was fracture toughness and crack growth rate. The fracture toughness and crack growth rate were conducted in accordance with AsTm standard E399-83 and ASTM standard E647-86a respectively. The test results show that the fracture toughness at the HAZ is slightly higher than at the base metal. The crack growth rate depends on the range of the stress intensity factor (AK). For low value of AK, the crack growth rate at the HAZ is 35%,i lower than at the base metal, and for high value of AK, it shows 46% lower than at the base metal.